Proposta de um padrão gerencial de gestão de portifólio de novos produtos para indústrias farmacêuticas nacionais - Raquel Assis Moreira (2008)
The selection of projects of new products is a complex process that involves many risks to the company. The New Product Portfolio Management aims at helping decision-makers select the new products with basis on important criteria for the company. It is known that the Brazilian pharmaceutical industry owns a poorly structured Product Development System, once it has gone through changes due to stricter sanitary requirements after the publication of the Generic Law in 1999. Considering this scenario, this paper seeks to show how the national pharmaceutical companies select and prioritize their new product development projects and proposes a structure that can help these companies select their products. For that purpose, the research was based on the multiple-case study methodology, and four different companies belonging to the categories of private companies and public laboratories have been investigated. The results of the field research confirm that these companies own a non-structured Product Development System and that the selection of projects of new products is made on a non-systemic basis. The results allowed the identification of important criteria for the selection of new pharmaceutical products in the national industry, which have been used for the preparation of a managerial standard for application of the New Product Portfolio Management in national pharmaceutical companies, taking into consideration the literature and the reality of the studied companies. The New Product Portfolio Management managerial standard for the National Pharmaceutical Industry is a systemic, flexible managerial model that requires practical application for its validation.